Satellite Remote Sensing of Rice Crops in Nepal : A Review - Magar, Keshav Thapa (Journal of Agriculture and Environment, 2023)
Remote sensing, based on satellite data, is useful in studying rice crops for their several parameters such as cropped area, crop-coverage, growth stages, production, yield estimation and other statistics useful in scientific investigations. Despite some satellite-remote-sensing based researches have been reported in the country, such appliance in agricultural studies is very sparse in Nepal. In the current situation, Nepal could benefit from remote sensing technology for betterment of its agricultural planning and development specifically in the rice sub-sector for its national economic and food security importance. This review article is an attempt to highlight the importance of rice remote sensing in Nepal and list research articles in the field as bookmarks to benefit future rice researchers and interested readership.